Evaluation of Dermal Toxicity and Wound Healing Activity of Cnestis ferruginea Vahl ex DC - Akosua Dufie Ankomah; Yaw Duah Boakye; Theresah Appiah Agana; Vivian Etsiapa Boamah; Paul Poku Sampene Ossei; Francis Adu; Christian Agyare (Advances in Pharmacological and Pharmaceutical Sciences)
Cnestisferruginea is a tropical plant, which is traditionally used in the treatment and management of various conditions including skin infections and wounds. The aim of this study was to investigate the dermal toxicity and wound healing potential of C. ferruginea. Ten millimeter full-thickness mucosal wounds were created on the dorsal midportion of the Sprague Dawley rats. Wounds were treated with 10, 5, and 2.5% w/w aqueous creams, prepared from the methanol extract of the root bark of C. ferruginea (CFM). The wound tissues were harvested on day 21 for histology studies. Compared with the untreated group, 10, 5, and 2.5% w/w CFM-treated wounds significantly reduced the wound size over the study period (P<0.0001). Tissue histology revealed a healed wound with well-regenerated collagen and skin appendages with no pus cells. A skin irritation test was conducted on CFM, as well as the dermal toxicity of CFM was determined in the repeated dose and acute dermal toxicity bioassays. These tests revealed that CFM showed no toxic effect on the skin and showed that CFM was not a skin irritant. C. ferruginea exhibited wound healing activity, which gives credence to its folkloric use.